Measuring the Work Values and work engagement of Employees: The Philippines Context - Abun, Damianus; Ruadap-Macaspac, Libertine Gertrude; Magallanes, Theogenia; Encarnacion, Mary Joy; Flores, Nathanael (Technium Social Sciences Journal, 2021)
This study intended to determine the influence of work values on work engagement. To enrich the discussion on this particular topic, the literature was reviewed and theories were proposed on extrinsic and intrinsic work values. The study was intended for the employees of Divine Word Colleges in the Ilocos Region, Philippines. To gather the data, questionnaires were used and in interpreting the data, descriptive and inferential statistics were used such as weighted mean and Pearson r Correlation. Weighted mean was used to determine the level of work values such as extrinsic, intrinsic work values, and work engagement. While Pearson e was used to determine the correlation between work values and work engagement. The study found that employees of Divine Word Colleges view both values to be important and are considered high and their work engagement is also considered high. Finally, the study found that there is a correlation between work values and work engagement. Therefore the hypothesis is accepted.